SHREWS: A game with augmented reality for training computational thinking - Saraiva, Francisco (2021)
This paper proposes a game to help young students training Computational Thinking (CT) skills to aid in solving problems. CT is a problem-solving approach based on picking a complex problem, understand what the problem is, and develop solutions in a way that a computer or human could solve. To help in this task, Augmented Reality(AR) will provide a more engaging visual way of interaction to keep students motivated while they search for solving problems. This benefit is a consequence of the AR capability of providing a visual and dynamic representation of abstract concepts. This work investigates AR and CT concepts and the best way of combining them for training student's skills to understand software and its effects. Thus, these concepts will be explored for the construction of learning activities to explain and create analogies to understand complex concepts related to computer programs. So the focus of the paper is the introduction of Shrews, the game created in this context. The principle and the proposed architecture are detailed. At the end, there is a description of how the game works and the current state of the prototype. We believe that the immersive experience using AR and CT concepts is one of the important aspects of the game to maintain a motivational approach to students. An exploratory prototype is created to explore the topic of teaching CT skills via playing a video game.